Estratégias analíticas para estudos de autenticação e controle de qualidade de produtos naturais - Hypericum perforatum e Lycium barbarum - Ana Gabriella Carvalho Miguita (2023)
Recently, the population's interest in medicines and natural supplements as substitutes for synthetic drugs has grown. However, there are several problems involving the high consumption of these products, such as the large number of cases of self-medication without medical supervision, and also the lack of inspection and quality control of these medicines, which may lead to instances of forgery and adulteration. Thus, the objective of this work was to analyze samples of two types of natural products to assess the authenticity and quality of these products. In the first application, 43 samples of Hypericum Perforatum L., known as St John's wort, were analyzed. Commercial samples were analyzed by paper spray mass spectrometry (PS-MS) and total reflection X-ray fluorescence (TXRF), and the resulting data were processed by chemometric tools. Through PS-MS spectra, it was possible to identify samples containing other active principles in addition to Hypericum perforatum. Therefore, 52.3% of the samples were detected as adulterated. Through TXRF data, it was possible to identify and quantify 19 elements present in the samples. PCA (Principal Component Analysis) models were built for the data obtained by PS-MS and for those obtained by TXRF, as well as a data fusion model, concatenating the results of the two techniques. In the second application, 28 commercial samples (in capsules) of Goji berry (Lycium barbarum) were analyzed by PS-MS. Likewise, through mass spectra, it was possible to detect the absence of compounds characteristic of the fruit in 18 samples, indicating cases of product counterfeiting. A PCA model was built from the data obtained to evaluate the dispersion of the samples. From the results obtained, one can verify the simplicity and applicability of the PS-MS technique for assessing the authenticity of herbal medicines and supplements and conclude that there is a clear need for greater quality control of these natural products in Brazil.